1994
DOI: 10.1016/s0248-4900(94)80004-9
|View full text |Cite
|
Sign up to set email alerts
|

The expression of carbonic anhydrases II and IV in the human pancreatic cancer cell line (Capan 1) is associated with bicarbonate ion channels

Abstract: Human pancreatic ductal cells of the Capan 1 cell line differentiate progressively during growth. After the exponential growth phase, the cells elongate and become polarized with their apical poles covered by microvilli and separated from the basolateral pole by tight junctions. In this stationary phase, they form domes, which are thought to result from the exchange of water and electrolytes. In this study, we demonstrated, using patch-clamp techniques, that HCO3- ions exit via the g350 high conductance anioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 39 publications
(80 reference statements)
4
34
0
Order By: Relevance
“…Recently, we reported that mRNA for CA IV and, to a lesser extent, CA VI are expressed in human pancreas as detected by Northern blotting and reverse transcription-polymerase chain reaction (RT-PCR) (7). CA IV has been found on the cell surface of cultured tumor cells from human pancreatic ductal carcinoma (8). We suspected there may be additional novel CA isozymes expressed in human pancreas and sought to clone them by RT-PCR with human pancreas poly(A) ϩ RNA using primers based on conserved amino acid sequences of two short regions of CA known isozymes (homology probing) (9 -11).…”
mentioning
confidence: 99%
“…Recently, we reported that mRNA for CA IV and, to a lesser extent, CA VI are expressed in human pancreas as detected by Northern blotting and reverse transcription-polymerase chain reaction (RT-PCR) (7). CA IV has been found on the cell surface of cultured tumor cells from human pancreatic ductal carcinoma (8). We suspected there may be additional novel CA isozymes expressed in human pancreas and sought to clone them by RT-PCR with human pancreas poly(A) ϩ RNA using primers based on conserved amino acid sequences of two short regions of CA known isozymes (homology probing) (9 -11).…”
mentioning
confidence: 99%
“…This increase was concomitant with the spontaneous and progressive acquisition of a differentiated cell stage. The existence of a relationship between the expression of CA II and differentiated cell status has also been demonstrated in other human pancreatic duct cell lines (Frazier et al 1990) and for enzyme systems such as alkaline phosphatases (Fanjul et al 1991) or CA IV (Mahieu et al 1994;Mairal et al 1996) in this same cell model. In the same way, CA II in vivo is considered to be a marker for the tissue differentiation of excretory ducts in the developing rat parotid gland (Peagler et al 1998).…”
Section: Discussionmentioning
confidence: 68%
“…On electron microscopic analysis, this immunoreactivity was localized essentially in apical plasma membranes. CA IV has also been found to be confined to these membrane domains (Mahieu et al 1994;Mairal et al 1996). Western blotting confirmed the specificity of the immunocytochemical reactions and provided further support for the presence of CA II associated with apical plasma membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capan-1 cells represent an excellent model for the in vitro study of human cancerous pancreatic duct cells, as despite their neoplastic transformation, they retain a polarized morphology and the ability to secrete HCO 3 À ions 55,56 and M1 mucins (MUC5AC). 57-59 These cells express Fas, but depending to authors, are sensitive [47][48][49] or resistant 50,51 to Fas-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 99%